The dama gazelles : last members of a critically endangered species - Mungall, Elizabeth Cary (W.L. Moody Jr. natural history series, 2018)
Finalist, 2019 Outstanding Publications Award, sponsored by the Texas Chapter of the Wildlife Society Dama gazelles, the largest of the gazelles, were once a common sight in Northern Africa, with a habitat ranging from the Atlantic Ocean east almost to the Nile River. Today, these animals are critically endangered as their populations have dropped precipitously due to the effects of expanding agrarian practices, overhunting, violent human conflict, and climate change on their native habitats. Though they are perilously close to extinction in the wild, Texas ranches maintain over a thousand dama gazelles?more than the number currently in zoos and in the wild combined. The habitat on some of these ranches resembles their natural range along the Sahara Desert of Northern Africa, making them suitable living spaces for damas. In The Dama Gazelles, Elizabeth Cary Mungall brings together experts from around the world and offers a comprehensive reference book on these animals, including information on natural history and taxonomy; physical and behavioral traits; dama gazelles held in zoos and collections, parks and preserves, and on Texas ranches; and efforts to reintroduce populations into the wild. There is also a rare, firsthand account from Frans M. van den Brink, an animal dealer from the Netherlands, who in the 1960s successfully captured 35 dama gazelles in Northern Africa and transported them to zoos in the United States and Europe, losing only two animals in the harrowing process. The remaining 33 eastern dama gazelles, plus four of the western dama gazelles gathered before their extinction in the wild, were the "founders" of all the dama gazelles in captivity today. Detailed appendixes and a glossary round out the volume with additional information to help researchers, zookeepers, and landowners better understand and conserve dama gazelles.